Perencanaan Strategis Sistem Informasi pada Web Perpustakaan Amikom Purwokerto - Fadilah Musafiroh; El Syafangatun Aulia Difa; Iis Sahita; Farah Setyaningsih (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
The rapid development of information technology has encouraged various organizations, including educational institutions, to utilize technology to support their operational activities. One form of information technology utilization in the academic field is the implementation of a web-based library information system. The Amikom Purwokerto library website faces several challenges in its use. One of the main problems encountered is the low level of user access, which is due to the users' limited understanding of the library website's usefulness and a lack of effective information regarding the available features. This situation creates a gap between user needs and the services provided, preventing the library from delivering optimal service. Therefore, strategic information system planning is needed by using the Ward and Peppard method and conducting an analysis using SWOT and Value Chain.